Characterization of Dry Noddles with Additional of Pedada (Sonneratia caseolaris) Mangrove Flour as Alternative Food Resource. Issue 1 (1st July 2022) - Muhammad, F; Andriyono, S; Pujiastuti, D Y
Abstract: Pedada fruit has a nutritional content that can be used as a food source because it contains high carbohydrates, but this fruit is easily spoiled because of the water content, which reaches 79%. Therefore, apple mangrove processing into flour to increase added value, one of the product is ingredient of the dried noodles. The purpose of this study was to investigate the nutritional content and panelist preference of dry noodles with addition of mangrove apple ( Sonneratia caseolaris ) flour with various concentrations. The research method used was experimental with a completely randomized design (CRD) as an experimental design. The treatment used was the substitution of mangrove apple powder ( Sonneratia caseolaris ), which is P0 (0%), P1 (5%) P2 (10%), and P3 (15%). The main parameter observed was the fibre content of dry noodles. The supporting parameters observed were proximate and organoleptic of dry noodle products. Data analysis used One Way Analysis of Variance (ANOVA) and followed by the further test of Least Significant Difference (LSD) 95%. The results showed that increasing the concentration of apple mangrove fruit flour ( Sonneratia caseolaris ) could increase the fiber content of dry noodles.